Analysis of Temple Management in the Educational Development of Interests and Talents - Chualasta, Silvia; Susanto, Susanto; Seneru, Wistina; Nyanabhadra, Phap Tu (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
The purpose of this research is to analyze how the management of the temple supports Buddhayana youth in developing their interests and talents, identify the factors that optimally influence the development of Buddhayana youth's interests and talents, and formulate practical solutions that can help Buddhayana youth face challenges in their self-development process. In addition, to analyze the management system processing at Bodhisattva temple. This research uses a qualitative approach with a descriptive nature and a case study method. Data collection was conducted through interviews, observations, and documentation with the Chairman of the Temple, Foundation Supervisors, and the Youth Leaders at Bodhisattva temple, Bandar Lampung in 2024. The research results show that the Buddhist Youth at Bodhisattva temple are actively involved in religious and social activities, such as Sunday School, major holiday celebrations, and blood donation drives, with a spirit of volunteerism based on the 5T principles: Sincerity, Intelligence, Mutual Assistance, and Responsibility. This participation is fully supported by the Temple management, which provides facilities, training, and logistics to support the development of their interests and talents. These activities enhance the skills, self-confidence, and leadership abilities of the youth, while also preparing them for a more mature future and strengthening the Buddhayana community at the temple.